Literature Review: Depresi Postpartum - Retno Arienta Sari (Jurnal Kesehatan, 2020)
Postpartum depression is a mood disorder that occurs after delivery. This disorder usually occurs around 2-6 weeks after giving birth. Research shows that the incidence of postpartum depression is 1 to 2 of 1000 births and that 25% of mothers who have just given birth experience severe postpartum depression and that in mothers giving birth to their next child around 20%. Symptoms of postpartum depression include depressed mood, loss of interest or pleasure in the activity, impaired appetite, sleep disturbance, physical agitation or psychomotor slowdown, weakness, feeling useless, difficulty concentrating, even suicidal ideation. It is important to do an early diagnosis of postpartum depression to both prevent and make symptoms worse. Mothers with postpartum depression need to get broad and maximum management from various parties, including families, closest people, and health workers from multidisciplinary sciences. In its handling, non-pharmacological therapies can be given such as psychological therapy and changes in daily behavior and also pharmacological therapies that previously need to be consulted to doctors such as tricyclic antidepressant drugs (TCAs) to reduce symptoms of postpartum depression.